Looking back to look ahead? Reviewing key lessons from Operation Lifeline Sudan and past humanitarian operations in South Sudan (Tufts Archival Research Center, 2018)
Looking back to look ahead? Reviewing key lessons from Operation Lifeline Sudan and past humanitarian operations in South Sudan. Working Paper 24, by Daniel Maxwell, Martina Santschi, and Rachel Gordon